2006
DOI: 10.1007/bf03165754
|View full text |Cite
|
Sign up to set email alerts
|

A halocin acting on Na+/H+ exchanger of Haloarchaea as a new type of inhibitor in NHE of mammals

Abstract: The capability of halocin H6 (a bacteriocin-like protein produced by haloarchaea Haloferax gibbonsii) to inhibit Na+/H+ exchanger (NHE) in mammalian cells and its cardio-protective efficacy on the ischemic and reperfused myocardium were evaluated in the present study. H6 inhibits NHE activity (measured by a flow cytometry method) in a dose-dependent form of cell lines of mammalian origin (HEK293, NIH3T3, Jurkat and HL-1) as well as in primary cell culture from human skeletal muscle (myocytes and fibroblasts). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…gibbonsii Ma2.39, from Spanish salt ponds in Alicante [37], was initially named halocin H7 in the first studies [22], and both nomenclatures are found in the literature. A halocin-overproducing mutant of the Ma2.39 strain, named strain Alicante SPH7 is also reported to produce HalH6 [37,38]. HalH6 was revealed by SDS-PAGE analysis to be a 32 kDa protein, but the amino acid sequence was not determined [36,37].…”
Section: Halocin H6mentioning
confidence: 95%
See 2 more Smart Citations
“…gibbonsii Ma2.39, from Spanish salt ponds in Alicante [37], was initially named halocin H7 in the first studies [22], and both nomenclatures are found in the literature. A halocin-overproducing mutant of the Ma2.39 strain, named strain Alicante SPH7 is also reported to produce HalH6 [37,38]. HalH6 was revealed by SDS-PAGE analysis to be a 32 kDa protein, but the amino acid sequence was not determined [36,37].…”
Section: Halocin H6mentioning
confidence: 95%
“…This transmembrane protein, which controls cytosolic pH and intracellular Na þ concentration in all living organisms, is of primary importance for Halobacteriales, where it constitutes the central unit for cell adaptation to highly saline environments [39]. Interestingly, a latter study showed that HalH6 could also inhibit the eukaryotic NHE [38], implying similarities in the structure of these proteins from the archaeal and the eukaryotic domains. It is currently unknown whether HalH6 has any effect on the function of this transporter in bacteria.…”
Section: Halocin H6mentioning
confidence: 95%
See 1 more Smart Citation
“…Some of these characterized halocines were isolated from Halobacterium, Haloferax, and other haloarchaeon strains and could have applications in this field (O'Connor and Shand, 2002;Shand and Leyva, 2007). Currently, halocins are not considered for use as antibiotics in medicine, but some experiments showed that they could be used as compounds for the control of blood pressure and related pharmacological uses, including potential applications for the reduction of injury in organ transplantation (Meseguer et al, 1995;Alberola et al, 1998;Lequerica et al, 2006;Shand and Leyva, 2007).…”
Section: Other Applicationsmentioning
confidence: 99%
“…This property can protect tissues including the myocardium from damage caused when blood returns after ischemic conditions. Currently, halocin H6 is the only known biological molecule that exerts a specific inhibitory effect on the NHE of mammalian cells (94).…”
Section: Medical Applicationsmentioning
confidence: 99%